Soil Fertility Mapping in Dindur Sub-Watershed of Karnataka for Site Specific Recommendations - Jahnavi Katti, I.N. Nagaral, P. Shikrashetti, H.M. Geetanjali and G.S. Dasog, P.L. Patil, V.B. Kuligod, S.S. Gundlur (Journal of the Indian Society of Soil Science, 2017)
Soil samples from Dindur sub-watershed in northern dry zone of Karnataka were drawn at 250 m grid interval and assessed for their fertility parameters. Analytical data was interpreted and statistical parameters like range, mean, standard deviation and coefficient of variation were calculated. Soil fertility maps were prepared for each parameter under GIS environment using Arc GIS v 10.4. Soils were neutral to very strongly alkaline with non-saline to slight salinity. Soil organic carbon content was low to medium. Available nitrogen (N) was low, available phosphorus (P) was low to medium, available potassium (K) was medium to high and sulphur (S) was low to medium. Regarding available micronutrients, zinc (Zn) and iron (Fe) were deficient in about half of the sub-watershed area whereas, copper (Cu) and manganese (Mn) were sufficient in the soils. The mapping of nutrients by GIS technique in the sub-watershed revealed that, available N, P, S, Zn and Fe are important soil fertility constraints.